Employees' use of mobile devices and their perceived outcomes in the workplace: A case of luxury hotel. (August 2016) - Jeong, Miyoung; Lee, Minwoo; Nagesvaran, Balendra
Abstract: This study attempts to identify employees' perceptions of using mobile devices and their perceived job performance when they use the mobile devices for their work at a hotel. Adopting the concept of self-efficacy from Bandura's social cognitive theory as a theoretical background, this study expands its conceptual framework by including two exogenous variables: job relevance and self-efficacy, facilitating condition as a moderator, and three endogenous variables: perceived job performance, job satisfaction and employee retention to scrutinize employees' psychological acceptance of the mobile device in the workplace. Findings of this study indicate that employees feel confident to use a mobile device at the hotel, think the mobile device is a relevant tool for performing their work better and ascertain the use of the mobile device improves their job performance, leading to increasing job satisfaction as well as retention with the current organization longer. Interestingly, no significant differences are found in employees' perceptions and psychological behavior of using mobile devices in the hotel by their job position and department. Discussions and suggestions for future research are provided.